Diorganyl Dichalcogenides and Copper/Iron Salts: Versatile Cyclization System To Achieve Carbo- and Heterocycles from Alkynes - Jurinic, Carla K.; Belladona, Andrei L.; Schumacher, Ricardo F.; Godoi, Benhur (Synthesis, 2021)
Organochalcogen-containing cyclic molecules have shown several promising pharmacological properties. Consequently, different strategies have been developed for their synthesis in the past few years. Particularly due to the low cost and environmental aspects, copper- and iron-promoted cyclization reactions of alkynyl substrates have been broadly and efficiently applied for this purpose. This short review presents an overview of the most recent advances in the synthesis of organochalcogen-containing carbo- and heterocycles by reacting diorganyl disulfides, diselenides, and ditellurides with alkyne derivatives in the presence of copper and iron salts to promote cyclization reactions.1 Introduction2 Synthesis of Carbo- and Heterocycles via Reactions of Alkynes with Diorganyl Dichalcogenides and Copper Salts3 Synthesis of Carbo- and Heterocycles via Reactions of Alkynes with Diorganyl Dichalcogenides and Iron Salts4 Conclusions
Keywords: copper; iron; organochalcogen; cyclization; carbocycles; heterocycles